The development of complexity at third-millennium BC al-Khashbah, Sultanate of Oman: results of the first two seasons, 2015 and 2016 - Schmidt, Conrad; Döpper, Stephanie (Proceedings of the Seminar for Arabian Studies, 2017)
The transition from the Hafit to the Umm an-Nar period on the Oman peninsula in the third millennium BC is regarded as a period of substantial social and economic change. Although many thousands of tombs from the Hafit period remain, other archaeological evidence, such as settlements, is scarce. In 2015 therefore, a new archaeological research project conducted by the University of Tübingen and funded by the German Research Foundation was launched at al-Khashbah to investigate its Hafit and Umm an-Nar period remains. During the first two seasons research consisted of an intensive field survey, aerial survey, two geophysical surveys, as well as archaeological excavations in selected areas within the site. Among other archaeological remains, al-Khashbah features three Hafit-period stone towers and six towers from the Umm an-Nar period, including the famous rectangular building. The most important discoveries are a Hafit-period settlement with monumental mud-brick architecture and a stone-built tower dating to the end of the fourth millennium BC, associated with the oldest evidence of copper processing in Oman. Both findings testify to the importance of al-Khashbah for the investigation of the development of complexity at the end of the fourth and the beginning of the third millennium BC.